Disordered Pancreatic Inflammatory Responses and Inhibition of Fibrosis in CD39-null mice - Künzli, Beat M. (2007)
BACKGROUND & AIMS: Extracellular nucleotides are released from injured cells and bind to purinergic-type 2 receptors (P2-R) that modulate inflammatory responses. Ectonucleotidases, such as CD39/NTPDase1, hydrolyze extracellular nucleotides to integrate purinergic signaling responses. As the role of extracellular nucleotides and CD39 in mediating inflammation and fibrosis are poorly understood, we studied the impact of CD39 gene deletion in a model of pancreatic disease. METHODS: Pancreatitis was induced by cyclosporine pretreatment, followed by cerulein injections (50 μg/kg, 6 i.p. injections daily, 3 times per week); mice were sacrificed at days 2, wk 3 and wk 6. Experimental parameters were correlated with cytokine levels in blood, mRNA and protein expression of purinergic and fibrosis markers in tissues. Immunohistochemistry and pancreatic morphometry of fibrosis were performed in wild-type and CD39-null mice. Effects of CD39 deletion on proliferation of primary pancreatic stellate cells (PSC) were investigated in vitro. RESULTS: Wild-type mice developed morphological features of pancreatitis with the anticipated development of parenchymal atrophy and fibrosis. CD39 and P2-R became overexpressed in vascular and adventitious wild type tissues. In contrast, CD39-null mice had inflammatory reactions but developed only minor pancreatic atrophy and limited fibrosis. Interferon-γ became significantly increased in tissues and plasma of CD39-null mice. Wild-type PSC expressed high levels of CD39 and P2-R. CD39-null PSC exhibited decreased rates of proliferation and the expression of procollagen-α1 was significantly inhibited in vitro (P<0.03). CONCLUSIONS: CD39 deletion decreases fibrogenesis in experimental pancreatitis. Our data implicate extracelluar nucleotides as modulators of PSC proliferation and collagen production in pancreatitis.